Effect of Colchicine Concentrations and Soaking Period on Ploidy of Katokkon Chili (Capsicum chinense Jacq.) at Seedlings Stage - Sjahril, Rinaldi; Riadi, Muhammad; Ridwan, Ifayanti; Kasim, Nurlina; Tambung, Astina; Novitasari, Novitasari (AGRIVITA Journal of Agricultural Science, 2024)
This research is conducted to study the induction of polyploidization in Katokkon chili using colchicine to study the effect of chromosome doubling or polyploid on certain superior characters during the seedling phase. Some morphological alterations were determined and proven to persist during the seedling phase. The study was conducted in the laboratory and screen house of the Department of Agronomy, Faculty of Agriculture, Universitas Hasanuddin. The polyploidy of the Katokkon chili is induced by soaking the germinated seeds in 0%, 0.05%, 0.1%, and 0.2% colchicine solutions for 6, 12, 24, and 48 hours each. Ploidy levels are analyzed using flow cytometry (Partec®Cy-Flow Space TM). Results show significant differences in colchicine treatment affecting all parameters observed: hypocotyl base of sprouts, plant height, stomata size, and the number of lateral shoots. Flow cytometry analysis histogram confirmed that administration of 0.1% colchicine concentration with 48 hours soaking time and 0.2% colchicine concentration with 24- or 48-hour soaking time can induce tetraploid plants (4n=48) with different coefficients of variance (CV-x%), 5.36%, 4.65%, 6.08%, respectively. Vigorous growth phenotype in leaf size and plant height was more clearly seen in the one-month-old tetraploid Katokkon chili seedlings induced by 0.10% with a soaking time of 48 hours.